Embedding spirituality in young children: an inter-generational challenge - Allana, Anila Rafiq (International journal of children's spirituality, 2017)
This study reports on the inter-generational transmission of faith values to young children (three to six years) from the perspectives of parents, grandparents, and religion teachers. The study was conducted at two religious education centres in Dar es Salaam, Tanzania. Through a qualitative rapid ethnographic approach (interviews, focus groups, and observations), we explored the practices and challenges in realizing the practice of faith as part of children's everyday life. Eleven themes elicited which were further reflected in three overarching trends - Building the foundation - on the right path'; Meeting the challenges-embedding faith'; Creating a conducive environment - brining us together'. Key findings revealed that although parents were keenly interested in spiritual development of their young children, they felt challenged by time deficits, multiple priorities, and secularization. Grandparents and religious education teachers were critical of the lack of parental commitment to spiritual development, seeing themselves often becoming surrogate drivers for this imperative. In conclusion, parents requested the institutions to schedule weekly practical classes in prayer and rituals. They also indicated that grandparents' involvement in religious education activities are enabling and supportive to the parents in nurturing children's spirituality. As a result there is a clear indication of the role for inter-generational involvements in embedding spirituality in young children.